Long-range interference of localized electromagnetic field enhancement in plasmonic nanofinger lattices - Sui, Yunxia; Hu, Pan; Pan, Dalong; Jiang, Zhanshuo; Song, Qianliang; Su, Guangxu; Wu, Wei; Liu, Fanxin (Frontiers in Physics, 2022)
Sub-wavelength strongly confined electromagnetic field induced by surface plasmon resonance offers a promising method to enhance the light-matter interactions, which has wide applications in the fields of enhanced spectroscopy, photovoltaic conversion, and photocatalysis. For periodic metal nanostructures, the localized surface plasmon resonance (LSPR) can couple with the long-range diffractive interaction, causing a narrow linewidth. Here, we report a new family of plasmonic nanostructure fabricated through nanoimprint lithograph, which enables completely uniform, reproducible, and low-cost Au nanofinger multimer arrays with high aspect ratio at the manufacturing scale. Through adjusting the lattice spacing and the angle of incident light, the different collective coupling strengths between the diffraction modes and the LSPR of trimer or pentamer Au nanofingers arrays are observed experimentally by angle-resolved reflection spectroscopy. According to the numerical simulation based on the finite element method, the dynamic evolution of collective coupled modes is demonstrated. The typical surface charge distribution and electric field distribution of the coupled dipole resonance show a significant electromagnetic field enhancement. By adjusting the height of nanofingers, lattice spacing and gap size of adjacent nanofingers, the feasibility of the coupled modes is further investigated. This work provides an excellent candidate for the localization of light as chip-scale plasmonic devices.